A Simple Quality Assessment Index for Stereoscopic Images Based on 3D Gradient Magnitude. (14th July 2014) - Wang, Shanshan; Shao, Feng; Li, Fucui; Yu, Mei; Jiang, Gangyi
Abstract : We present a simple quality assessment index for stereoscopic images based on 3D gradient magnitude. To be more specific, we construct 3D volume from the stereoscopic images across different disparity spaces and calculate pointwise 3D gradient magnitude similarity (3D-GMS) along three horizontal, vertical, and viewpoint directions. Then, the quality score is obtained by averaging the 3D-GMS scores of all points in the 3D volume. Experimental results on four publicly available 3D image quality assessment databases demonstrate that, in comparison with the most related existing methods, the devised algorithm achieves high consistency alignment with subjective assessment.